Imagined Futures: Trust and Justice in Synthetic Biology Governance - Siewert, Stephanie; Kieslich, Katharina; Braun, Matthias; Dabrock, Peter (Springer Science and Business Media B.V., 2023)
The chapter discusses social and cultural implications and current areas of conflict in synthetic biology. Since there is the challenge of potentially misleading imaginaries and an overall uncertainty regarding research and application in the field, it is quintessential to consider the category of social trust as an underlying value that shapes our perception and acceptance of SB. Trust in synthetic biology cannot simply be guaranteed or established, but remains fragile. At the same time, there are conditions which make a leap of faith more likely. A central component of this is participation and a structure of governance that is aligned to an understanding of the complexity of negotiations between science, society, and economy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Bioeconomy; Imaginaries of Synthetic Biology; Precaution; Risks; Trust